Relationship Breast Care in Pregnancy yo Breast Milk Production in Post Partum Mothers - Rici Gusti Maulani; Yulinda Laska; Liontin Valentina Febriani (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Mother's milk is the best food for babies because it contains all the nutrients in the amount needed by babies to grow and develop optimally, especially aged 0-6 months. The obstacle to early breastfeeding is due to the small production of breast milk caused by mothers who do not take care of their breasts during pregnancy. Breast care is a good preparation for mothers to breastfeed their babies. The purpose of this study was to determine the relationship between breast care during pregnancy and milk production in post partum mothers. This research method uses a quantitative approach, the sampling technique used is non-probability sampling (purposive sampling) with a sample size of 37 respondents. In this study using a checklist sheet instrument, then the method of data analysis using the chi-square statistical test. The results of this study were 15 post partum mothers breastfeeding was not smooth due to not doing breast care, 3 (20%) out of 15 post partum mothers breastfeeding were not smooth but still doing breast care. Furthermore, there were 22 post partum mothers whose milk production was smooth, 20 (90.9%) of the 22 post partum mothers whose milk production was smooth due to breast care, then 2 (9.1%) of the 22 post partum mothers their milk production was smooth but not doing breast care. The results of the chi-square statistical test with a p-value of 0.000<0.005 showed that there was a significant relationship between breast care during pregnancy and post partum mother's milk production at PMB Atlantika Amd.Keb, Batam City.